2002
DOI: 10.1091/mbc.02-02-0012
|View full text |Cite
|
Sign up to set email alerts
|

MEC3,MEC1,andDDC2Are Essential Components of a Telomere Checkpoint Pathway Required for Cell Cycle Arrest during Senescence inSaccharomyces cerevisiae

Abstract: When telomerase is absent and/or telomeres become critically short, cells undergo a progressive decline in viability termed senescence. The telomere checkpoint model predicts that cells will respond to a damaged or critically short telomere by transiently arresting and activating repair of the telomere. We examined the senescence of telomerase-deficient Saccharomyces cerevisiae at the cellular level to ask if the loss of telomerase activity triggers a checkpoint response. As telomerasedeficient mutants were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
151
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(169 citation statements)
references
References 59 publications
(95 reference statements)
17
151
1
Order By: Relevance
“…We have also found that the increase in telomeric silencing seen in the absence of ELG1 depended on yKu70p, which is known to recruit the Sir complex to the telomeres (15,39), and on Sir2p, a major component of the telomeric silencing complex (40). Elg1p probably affects silencing directly because we have shown that the telomere position effect enhancement in ⌬elg1 strains is not a consequence of telomere elongation.…”
Section: Discussionmentioning
confidence: 58%
“…We have also found that the increase in telomeric silencing seen in the absence of ELG1 depended on yKu70p, which is known to recruit the Sir complex to the telomeres (15,39), and on Sir2p, a major component of the telomeric silencing complex (40). Elg1p probably affects silencing directly because we have shown that the telomere position effect enhancement in ⌬elg1 strains is not a consequence of telomere elongation.…”
Section: Discussionmentioning
confidence: 58%
“…This nucleoprotein complex protects the ends of chromosomes from being recognized as double-strand breaks, thereby preventing recombination between telomeres that leads to chromosomal fusions and instability (11,12). In the absence of telomerase, telomeres shorten with every round of DNA replication, eventually reaching a critically short length that triggers arrest in the G 2 ͞M stage of the cell cycle (13)(14)(15)(16). Although the majority of cells cease dividing after 50-100 generations, a fraction of cells escape arrest by forming alternative telomere structures containing either tandem arrays of the subtelomeric repeat, YЈ (type I survivors), or long and heterogeneous tracts of telomeric repeat DNA (type II survivors) (14,17,18).…”
mentioning
confidence: 99%
“…The signaling pathway that triggers G 2 ͞M arrest in response to telomere shortening has recently been defined (15,16). The ''telomere checkpoint pathway,'' which is a segment of the DNA-damage checkpoint pathway (reviewed in refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many decades later, telomeres were identified as the structures at the ends of chromosomes whose function is to stabilize these chromosomes and prevent stepwise loss of genetic material as a result of the incomplete replication of DNA strands with each round of replication. The discovery of the ribonucleoprotein telomerase, with its enzyme-associated RNA template, which recognizes and extends the G-rich strand of the terminal repeat by adding T-G polydeoxyribonucleotide repeats, came from studies of the ciliate Tetrahymena, but this insight was soon expanded by studies of telomeres and the proteins involved in telomere function in S. cerevisiae by laboratories of V. A. Zakian, B. Tye, Judith Berman, J. E. Haber, E. H. Blackburn, D. Shore, and many others (Enomoto et al, 2002).…”
Section: Chromosomes and Telomeresmentioning
confidence: 99%